2023
DOI: 10.2196/45943
|View full text |Cite
|
Sign up to set email alerts
|

Global, Regional, and National Prevalence of Gout From 1990 to 2019: Age-Period-Cohort Analysis With Future Burden Prediction

Abstract: Background Gout is a common and debilitating condition that is associated with significant morbidity and mortality. Despite advances in medical treatment, the global burden of gout continues to increase, particularly in high–sociodemographic index (SDI) regions. Objective To address the aforementioned issue, we used age-period-cohort (APC) modeling to analyze global trends in gout incidence and prevalence from 1990 to 2019. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
1
6
0
1
Order By: Relevance
“…In terms of incidence, the ASIR was higher among female individuals than among male individuals in 2019. This was consistent with the results of previous studies [ 11 , 26 ]. In 2015, a systematic review of prevalence studies showed that female individuals were twice as likely as male individuals to have ADs [ 4 ], which indicated that more female individuals are affected by ADs than male individuals worldwide.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In terms of incidence, the ASIR was higher among female individuals than among male individuals in 2019. This was consistent with the results of previous studies [ 11 , 26 ]. In 2015, a systematic review of prevalence studies showed that female individuals were twice as likely as male individuals to have ADs [ 4 ], which indicated that more female individuals are affected by ADs than male individuals worldwide.…”
Section: Discussionsupporting
confidence: 94%
“…This study predicted the incidence rate of ADs from 2020 to 2044 by running a Nordpred age-period-cohort analysis by sex using the Nordpred package in R (R Foundation for Statistical Computing), accounting for changing rates and changing population structures. This method has been fully demonstrated and recognized in previous studies [ 26 ].…”
Section: Methodsmentioning
confidence: 96%
“…The highest incidence of CVD was in the age group of 50-70 years old, accounting for about half in all. 40 In addition, although the prevalence of COPD in China is lower than in western countries, its mortality rate is signi cantly higher. 41 Early screening for "big-3 diseases" can slow down disease progression and reduce their mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, its incidence rate is continuously increasing. According to the Global Burden of Disease Study 2019, the global incidence of gout has increased by 63.44% over the past 20 years, resulting in a 51.12% increase in the number of years lived with a disability [ 3 ]. Gout is associated with various systemic and metabolic diseases, including cardiovascular disease, chronic kidney disease, neurodegenerative diseases, diabetes, osteoporosis, and metabolic syndrome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%